Improvement of delayed fracture resistance on chrome molybdenum steel bolt by cavitation peening - Naoki KUMAGAI; Osamu TAKAKUWA; Hitoshi SOYAMA (Nihon Kikai Gakkai ronbunshu, 2016)
In order to demonstrate the effect of cavitation peening on crack initiation stage of hydrogen-charged materials with the objective of industrial application, and suppression of the delayed fracture of bolt, the delayed fracture test was conducted under constant load after hydrogen charging. The obtained results show that fracture surface at an origination of the delayed fracture took on intergranular fracture, and fracture occurred in a moment after crack initiate from stress concentration portion such as root of thread potion and incomplete thread. That is to say, evaluation of crack initiation stage of hydrogen-charged materials can be achieved by the delayed fracture test. Threshold stress σth of the delayed fracture was increased by cavitation peening and kept on increasing with processing time of cavitation peening. σth increased from 327 ± 22 MPa to 505 ± 42 MPa due to cavitation peening with tp = 6 s/mm. This effect was caused by introduction of compressive residual stress at root of thread potion, where subject to be fracture origin.